2015
DOI: 10.1021/acs.jpca.5b07079
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectroscopy Reveals Varying Structural Motifs in Cu+(CH4)n and Ag+(CH4)n (n = 1–6)

Abstract: Vibrational spectra are measured for Cu(+)(CH4)(Ar)2, Cu(+)(CH4)2(Ar), Cu(+)(CH4)n (n = 3-6), and Ag(+)(CH4)n (n = 1-6) in the C-H stretching region (2500-3100 cm(-1)) using photofragment spectroscopy. Spectra are obtained by monitoring loss of Ar or CH4. Interaction with the metal ion produces substantial red shifts in the C-H stretches of proximate hydrogens. The magnitude of the shift reflects the metal-methane distance and the coordination to the metal ion of the methane hydrogens (η(2) or η(3)). The struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 54 publications
(88 reference statements)
5
33
0
Order By: Relevance
“…Qualitatively similar features within the same IR range have also been observed in the IR depletion spectra of the other d 10 metal cation complexes, Cu + (CH 4 ) 4−6 and Ag + (CH 4 ) 5−6 recorded previously by Metz et al [ 78 ]. However, for n = 3 the IR depletion spectra presented here for the gold complexes differ significantly from those of the other coinage metals indicating a markedly different binding motif.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Qualitatively similar features within the same IR range have also been observed in the IR depletion spectra of the other d 10 metal cation complexes, Cu + (CH 4 ) 4−6 and Ag + (CH 4 ) 5−6 recorded previously by Metz et al [ 78 ]. However, for n = 3 the IR depletion spectra presented here for the gold complexes differ significantly from those of the other coinage metals indicating a markedly different binding motif.…”
Section: Resultssupporting
confidence: 84%
“…The Fe + , Co + and Ni + ions, with their 3 d n ground state configurations, interact with methane more strongly than ions with 3 d n −1 4 s 1 configurations, such as Mn + (CH 4 ) 1−6 . IR photofragmentation spectroscopy studies have also been performed on the d 10 complexes Cu + (CH 4 ) 1−6 and Ag + (CH 4 ) 1−6 [ 78 ], which tend to possess highly-symmetrical structures due to the spherical nature of the ion. The latter studies inspired the work presented here as part of our own development of a metal–ligand complex infrared dissociation instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopy of transition metal-hydrocarbon radicals or ions formed in gas phase reactions has recently attracted considerable attention. Metal ion-hydrocarbon species are largely investigated by infrared or ultraviolet-visible photodissociation or photoelectron spectroscopy, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] whereas metal atomhydrocarbon radicals are mainly studied by resonant twophoton ionization and dispersed fluorescence, [21][22][23][24] Fourier transform microwave, 25 and mass-analyzed threshold ionization (MATI) spectroscopy. [26][27][28][29][30][31][32][33] Spectroscopic measurements probe the state specific energetics and structures of shortlived species, which are vital for gaining insight into reaction mechanisms and electronic and structural characteristics for efficient bond activation at metal centers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although a large body of thermodynamic and kinetic data is now available in the literature for gas-phase metal-hydrocarbon reactions as shown by numerous reviews, [6][7][8][9][10][11][12][13][14][15][16] spectroscopic measurements of metal-hydrocarbon species are lagged behind. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] As one of the simplest alkene molecules and the most important raw chemicals in petrochemical industry, metal-mediated propene activation has received considerable attentions. [6][7][8][9][10]14,15 For rare earth metal-propene reactions, previous studies have been reported on the product distributions and kinetics of both neutral atoms and positively charged ions.…”
Section: Introductionmentioning
confidence: 99%